KINERJA DAN MULTIFUNGSIONALITAS USAHATANI PADI ORGANIK DAN KONVENSIONAL DI PROVINSI JAWA TENGAH - , Tinjung Mary Prihtanti, SP.MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Agricultural activity is no longer only valued for its contribution to food production, but needs to be assessed according to a much wider range of social and environmental concerns, which are known as multifunctionality of agriculture. The objective of this study was to compare farming performance, namely productivity, R/C ratio, technical efficiency, allocative efficiency, economics efficiency, environmental efficiency, and farming multifunctionality, namely food sufficiency, farmerâs cohessiveness, women participation, farming tradition, soil quality, biodiversity, pollution avoidance, between organic rice farming system and conventional systems. The study was conducted at Pereng, Mojogedang, Karanganyar District, and Sukorejo, Sambirejo, Sragen District. Respondents were classified into organic rice farmers that didnât using any chemical inputs with 37 farmers, and conventional rice farmer, which using chemical inputs) some 80 farmers. Several methods were applied, namely SFA (stochastic frontier analysis), descriptive statistic, and canonical correlation. The result revealed that : (1) the nitrogen pollution as seen from the amount of nitrogen surplus, of organic rice farming system is lower than conventional system, but it was not affect farm productivity performance, (2) organic rice farming performance, there were productivity, R/C ratio, technical efficiency, allocative efficiency, economic efficiency, and environmental efficiency of was higher than conventional systems, (3) organic rice farming system multifunctionality, namely farmerâs cohesiveness, soil quality, biodiversity, pollution avoidance, was better than the conventional system, but household food sufficiency, women farmers participation, and frequency of farming tradition between the two farming systems were not statistically different, (4) economic value of food production function and the employment function of organic rice farming system was higher than conventional rice farming systems, (5) There was a strong relationship between farming performance and farming multifunctionality, both on organic rice farming system and conventional system.